Treatment of a severe distal thoracic and abdominal coarctation with cutting balloon and stent implantation in an infant: From fetal diagnosis to adolescence. Issue 3 (25th April 2022) - Carbonez, Karlien; Kefer, Joëlle; Sluysmans, Thierry; Moniotte, Stephane
Abstract: Background and Aims: Abdominal coarctations are rare. Surgical treatment is difficult and requires re‐interventions to adjust the graft material to patient growth. We report effective treatment by interventional catheterization in an infant with the concern to allow adjustment for growth and prevention of vessel damage. Methods and Results: After the diagnosis of abdominal coarctation at 27 weeks of gestation, an infant developed hypertension (170/70 mmHg) at 3 months of age despite medical therapy. Angio CT confirmed a 2 mm diameter, 2.3‐cm‐long coarctation of the descending aorta. At 4 months, a dilatation was performed using a 3 mm cutting balloon and a 5 mm Opta® balloon, Cordis®. Two noncovered Palmaz® Genesis™ XD PG1910P stents were required to keep the aortic lumen open. At 15 months, an Adventa™ V12 vascular 12 × 61 mm long covered stent was implanted to exclude an aneurysm which developed between the two stents. At 3 and 9.5 years, the stents were further dilated with a high‐pressure balloon to reach 11 mm aortic diameter with no residual pressure gradient, and normal blood pressure. Conclusions: The use of cutting balloons and stent implantation is an effective way to relieve severe obstruction in middle aortic syndrome in neonates. The technical issues encountered were the need for a low profile sheath and material to avoid femoral artery damage, and the need to use stents that can be further expanded to adult size.